2021
DOI: 10.1080/17435390.2021.1931724
|View full text |Cite
|
Sign up to set email alerts
|

Issues currently complicating the risk assessment of synthetic amorphous silica (SAS) nanoparticles after oral exposure

Abstract: Synthetic amorphous silica (SAS) is applied in food products as food additive E 551. It consists of constituent amorphous silicon dioxide (SiO 2 ) nanoparticles that form aggregates and agglomerates. We reviewed recent oral toxicity studies with SAS. Some of those report tissue concentrations of silicon (Si). The results of those studies were compared with recently determined tissue concentrations of Si (and Si-particles) in human postmortem tissues. We noticed inconsistent results of the various toxicity stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…Finally, it may be worth mentioning that the risk assessment of oral exposure to amorphous silica NFs present in foods remains greatly uncertain due to technical drawbacks (silicon detection, contaminants, exposure mode) that must still be solved [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, it may be worth mentioning that the risk assessment of oral exposure to amorphous silica NFs present in foods remains greatly uncertain due to technical drawbacks (silicon detection, contaminants, exposure mode) that must still be solved [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…The presence of silica in sediments and soil helps strengthen the plant's cells and reduce water loss in agriculture. It also increases the plant tolerance, frost, and lodging action on the plants (Brand et al 2021;Barbhuiya et al 2021). In general, sandy soil contain a higher percentage of silica content.…”
Section: Silicamentioning
confidence: 99%
“…Recent some research showed the potential toxicity of SAS in terms of inflammation of the intestinal wall and neurotoxicity [ 15 , 16 , 17 , 18 ]. Contradictory in vivo toxicity results were also reported, showing the low oral toxicity of SAS [ 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 94%